Epistatic interaction between MyD88 and TIRAP against Helicobacter pylori. Issue 14 (27th June 2016) - Fulgione, Andrea; Di Matteo, Antonio; Contaldi, Felice; Manco, Rosanna; Ianniello, Flora; Incerti, Guido; De Seta, Massimiliano; Esposito, Nicolino; Crasto, Antonio; Iannelli, Domenico; Capparelli, Rosanna
Abstract : The genes MyD88 and TIRAP encode the adaptor proteins MyD88 and TIRAP. TIRAP plays the crucial role of activating the MyD88‐dependent pathway, which in turn controls the immune response (innate and adaptive) to Helicobacter pylori . We looked for an association of MyD88 and TIRAP with H. pylori infection. Cases and controls were genotyped at the polymorphic sites MyD88 rs6853 and TIRAP rs8177374 by real‐time PCR. When the genes were analyzed separately, only TIRAP was associated with infection. When the genes were analyzed concurrently, certain combinations of MyD88 and TIRAP protected the host against H. pylori colonization more efficiently than could be done by TIRAP alone. Abstract :